Peranan Workplace Trust dan Psychological Capital Terhadap Workplace Well Being Pada Karyawan Perusahaan X - Zamralita; Sinta Dewi Yuniarti (Reslaj: Religion Education Social Laa Roiba Journal, 2025)
Human Resources (HR) has a very important role in business development. Human resources who have relevant skills and competencies needed to carry out business tasks are valuable assets for the company. For this reason, the method used is to provide welfare programs to employees to maintain and improve the physical and mental conditions of employees so that their work productivity increases. In this study, Workplace Trust and Psychological Capital are used as independent variables that contribute to workplace well-being. In this study the sampling method used is purposive sampling. after taking 350 samples and then collecting data. The data analysis method used to examine the influence of workplace trust and psychological capital on workplace well-being is multiple linear regression analysis. The research results indicate a significant influence of the variables Workplace Trust and Psychological Capital on Workplace Well-Being, with a significance value of < 0.05.